Silicon Betavoltaic Batteries Structures - V.N. Murashev; S.A. Legotin; O.I. Rabinovich; O.R. Abdulaev; U.V. Osipov (Журнал нано- та електронної фізики)
For low-power miniature energy creation sources the particular interest is nickel Ni63. This paper discusses the main types of betavoltaic battery structures with the prospects for industrial application using - isotope of nickel Ni63. It is shown that the prospects for improving the effective efficiency are planar multijunction betavoltaic batteries.